A needs analysis for the development of e-modules project-based learning - Rahayu, Ismi; Sukardi, Sukardi (Jurnal Pendidikan Teknologi Kejuruan, 2020)
This research aims to describe the results of the needs analysis for the development of electronic module project- based learning. This research was a qualitative descriptive study by using survey methods in identifying the needs of students and teachers in learning assessment. In this research, needs analysis refers to the achievement of student learning outcomes, problems faced by students, and the media needed in the learning assessment process. This research used observation and interview methods in collecting the data. Observations and interviews were done for the students of grade X of computers and basic networks subject at SMKN 5 Padang. The results showed that: 1) completeness of student learning 2) Interactive learning media needed on computer and basic networks subject. The results of this research concluded that students need interactive learning media in learning activities. Thus, this research is used in designing electronic module project based learning.